Republic of Croatia : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Payments Systems, Securities Regulation, Insurance Regulation, and Monetary and Financial Policy Transparency. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents key findings of the Financial System Stability Assessment for the Republic of Croatia, including Reports on the Observance of Standards and Codes on Banking Supervision, Payments Systems, Securities Regulation, Insurance Regulation, and Monetary and Financial Policy Transparency. The financial system of Croatia is now more resilient and seems better prepared to cope with moderate shocks. The larger banks are generally better capitalized, and their risk management capacity has improved. The economy, however, remains highly euroized and susceptible to shifts in residents' sentiments toward the local currency.